The mystery of mitochondria-ER contact sites in physiology and pathology: A cancer perspective - Simoes, Ines C M (2020)
Mitochondria-associated membranes (MAM), physical platforms that enable communication between mitochondria and the endoplasmic reticulum (ER), are enriched with many proteins and enzymes involved in several crucial cellular processes, such as calcium (Ca2+) homeostasis, lipid synthesis and trafficking, autophagy and reactive oxygen species (ROS) production. Accumulating studies indicate that tumor suppressors and oncogenes are present at these intimate contacts between mitochondria and the ER, where they influence Ca2+ flux between mitochondria and the ER or affect lipid homeostasis at MAM, consequently impacting cell metabolism and cell fate. Understanding these fundamental roles of mitochondria-ER contact sites as important domains for tumor suppressors and oncogenes can support the search for new and more precise anticancer therapies. In the present review, we summarize the current understanding of basic MAM biology, composition and function and discuss the possible role of MAM-resident oncogenes and tumor suppressors.